Mature Peripheral RPE Cells Have an Intrinsic Capacity to Proliferate; A Potential Regulatory Mechanism for Age-Related Cell Loss - Kokkinopoulos, Ioannis; Shahabi, Golnaz; Colman, Alan; Jeffery, Glen (PLOS ONE, 2011)
Background Mammalian peripheral retinal pigmented epithelium (RPE) cells proliferate throughout life, while central cells are senescent. It is thought that some peripheral cells migrate centrally to correct age-related central RPE loss. Methodology/Principal Findings We ask whether this proliferative capacity is intrinsic to such cells and whether cells located centrally produce diffusible signals imposing senescence upon the former once migrated. We also ask whether there are regional differences in expression patterns of key genes involved in these features between the centre and the periphery in vivo and in vitro. Low density RPE cultures obtained from adult mice revealed significantly greater levels of proliferation when derived from peripheral compared to central tissue, but this significance declined with increasing culture density. Further, exposure to centrally conditioned media had no influence on proliferation in peripheral RPE cell cultures at the concentrations examined. Central cells expressed significantly higher levels of E-Cadherin revealing a tighter cell adhesion than in the peripheral regions. Fluorescence-labelled staining for E-Cadherin, F-actin and ZO-1 in vivo revealed different patterns with significantly increased expression on central RPE cells than those in the periphery or differences in junctional morphology. A range of other genes were investigated both in vivo and in vitro associated with RPE proliferation in order to identify gene expression differences between the centre and the periphery. Specifically, the cell cycle inhibitor p27Kip1 was significantly elevated in central senescent regions in vivo and mTOR, associated with RPE cell senescence, was significantly elevated in the centre in comparison to the periphery. Conclusions These data show that the proliferative capacity of peripheral RPE cells is intrinsic and cell-autonomous in adult mice. These differences between centre and periphery are reflected in distinct patterns in junctional markers. The regional proliferation differences may be inversely dependent to cell-cell contact.